Congenital pouch colon anorectal atresia combined with appendix duplication complicated by intestinal volvulus - A. Klokkaris; A. Pegios; Ch. Chaidos; A. Tzantzaroudi; G. Tsikopoulos (Elsevier, 2015)
Congenital pouch colon (CPC) is a rare abnormality with few reports in Europe, frequently detected in the Indian Peninsula, where it constitutes 15% of all anorectal malformations (ARM). This report presents a congenital pouch colon case combined with appendix duplication (AD) further complicated by midgut volvulus and intends to place emphasis on their concurrence.